Friends' networks and job finding rates - Lorenzo Cappellari; Konstantinos Tatsiramos (Institute for the Study of Labor (IZA), 2010)
We investigate the effect of social interactions on labor market outcomes using a direct measure of social contacts based on information about individuals' three best friends and their characteristics. We examine the effect of the number of employed friends on the transition from non-employment to employment, and we find the existence of significant network effects at the individual level. An additional employed friend increases the probability of finding a job by 3.7 percentage points. This finding is robust to specifications that address the endogeneity of friends' employment status, which may be induced by correlation with unobserved individual attributes and feedback effects. Considering labor market outcomes, we find evidence of higher wages and employment stability for those with more employed friends, which is consistent with networks acting as an information transmission mechanism.
Keywords: J64; 330; networks; unemployment; friendship ties